Initial Weekly HRV Response is Related to the Prospective Change in VO2max in Female Soccer Players - Esco, M. R.; Flatt, A. A.; Nakamura, F. Y. (International Journal of Sports Medicine, 2016)
The aim of this study was to determine whether the early response in weekly measures of HRV, when derived from a smartphone application, were related to the eventual change in VO2max following an off-season training program in female soccer athletes. 9 female collegiate soccer players participated in an 11-week off-season conditioning program. In the week immediately before and after the training program, each participant performed a test on a treadmill to determine maximal oxygen consumption (VO2max). Daily measures of the log-transformed root mean square of successive R-R intervals (lnRMSSD) were performed by the participants throughout week 1 and week 3 of the conditioning program. The mean and coefficient of variation (CV) lnRMSSD values of week 1 showed small (r=− 0.13, p=0.74) and moderate (r=0.57, p=0.11), respectively, non-significant correlations to the change in VO2max at the end of the conditioning program (∆VO2max). Significant and near-perfect correlation was found between the change in the weekly mean lnRMSSD values from weeks 1 and 3 (∆lnRMSSDM) and ∆VO2max (r=0.90, p=0.002). The current results have identified that the initial change in weekly mean lnRMSSD from weeks 1 to 3 of a conditioning protocol was strongly associated with the eventual adaptation of VO2max.
Keywords: parasympathetic; autonomic; female athletes; athlete monitoring